MOF-based sulfur polymer composite material as well as preparation method and application thereof

The combination of defective MOF808@PAA material and sulfur polymer prepared by using solvent thermal method in lithium sulfur batteries is formed to form a MOF-based sulfur polymer composite material, which solves the problem of deterioration in lithium sulfur batteries and achieves better electrodes Capacity maintenance and cycle stability.

CN119161743APending Publication Date: 2024-12-20HENAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411373541.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The rapid decline in the performance of lithium-sulfur batteries is mainly due to the poor conductivity and large volume changes of sulfur electrodes, which leads to the shuttle effect of soluble lithium polysulfide, which limits its wide commercial application.

Method used

The defective MOF808@PAA material was prepared by solvent thermal method, and sulfur polymer was introduced to form MOF-based sulfur polymer composite material. By introducing defects, the pore size distribution and porosity of the frame structure are improved, the catalytic conversion kinetics of LiPS were promoted, and the catalytic conversion kinetics of LiPS were inhibited. Dissolution and shuttle effect of lithium sulfide.

Benefits of technology

It effectively inhibits the dissolution and shuttle effect of lithium polysulfide, improves the uniform distribution of sulfur and the capacity retention rate of electrodes, extends the cycle life of the battery, optimizes the transmission of electrons and ions, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161743A_ABST
    Figure CN119161743A_ABST
Patent Text Reader

Abstract

The invention provides an MOF-based sulfur polymer composite material and a preparation method and application thereof.The preparation method includes the steps that a zirconium-based metal organic framework material MOF808-coated PAA is prepared through a solvothermal method, then 5-aminoisophthalic acid is added, defect-NH2 is introduced to prepare a defect type MOF808-D-coated PAA material, and finally the defect type MOF808-D-coated PAA material is combined with S to form the MOF-based sulfur polymer composite material MOF808-D-coated PS. According to the invention, defects are introduced into an MOF808-coated PAA organic frame structure, so that the porosity is improved, uniform distribution of sulfur is ensured, and the adsorption effect and catalytic conversion kinetics of LiPS are greatly enhanced by exposure of a large number of Zr metal nodes. Besides, based on the unique design of an MOF808-D molecular framework and taking a PAA carbon chain as a main chain, high-efficiency loading of active sulfur can be realized, electron / ion transmission can be accelerated, permeation of electrolyte can be promoted, reaction kinetics in the practical application process can be optimized, catalytic conversion kinetics can be promoted, and the catalytic conversion effect on LiPS can be promoted; and the serious dissolution and shuttle effects of LiPS are inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-sulfur batteries, in particular to a MOF-based sulfur polymer composite material and a preparation method and application thereof. Background Art

[0002] Lithium sulfur (Li-S) has a theoretical specific capacity of 1680 mAh / g, which is the composite material with the highest specific capacity among all known solid-state rechargeable positive electrode materials, much higher than traditional transition metal oxide positive electrode materials (theoretical specific capacity generally does not exceed 300 mAh / g). In addition, the theoretical energy density of lithium-sulfur secondary batteries is as high as 2600 Wh / kg, which is much higher than the specific energy of 350 Wh / kg, which is a long-term development indicator of electric vehicle power sources in practical applications. At the same time, the operating voltage of lithium-sulfur batteries is around 2.1 V, which is moderate, avoiding the decomposition of the electrolyte caused by high voltage, and has a good safety advantage. In addition, sulfur is a material that is abundant in source, low in price, and environmentally friendly.

[0003] However, the widespread commercialization of lithium-sulfur batteries is hampered by limited rate performance, rapid performance degradation due to poor conductivity of the sulfur electrode, large volume change (about 80%), and dissolution of intermediate products (lithium polysulfides) during cycling. Among these problems, the shuttle effect of dissolved lithium polysulfides is considered to be the main reason for the deterioration of lithium-sulfur battery performance. Therefore, inhibiting the shuttle effect of soluble lithium polysulfides in the battery system is the key to realizing the application of lithium-sulfur batteries.

[0004] In recent years, there has been an increasing amount of research on the preparation of lithium-sulfur batteries and their application in cathode materials for lithium-ion batteries. An effective way to suppress the shuttle effect of soluble lithium polysulfides in battery systems is to confine active sulfur in nanostructured carbon-based materials to increase the physical adsorption of polysulfides. To this end, coating strategies and absorption methods have been developed to enhance adsorption while reducing the shuttling of soluble polysulfides. Although similar approaches are widely used in lithium-sulfur batteries, it is difficult to obtain the performance required for practical applications by controlling the morphology and nanostructure of carbon-based materials. In addition, nanoscale sulfides tend to aggregate into larger particles, especially for larger sulfur contents, resulting in severe performance deterioration over time during electrochemical cycling. Another effective approach is to introduce organic sulfur by connecting sulfur chains through organic functional groups to increase the sulfur content while limiting the shuttling effect of lithium polysulfides. Although the formation of polysulfanes significantly increases the sulfur content and thus the capacity of the electrode, these sulfur chains are easily decomposed during discharge, and the electrode performance is still limited by the poor conductivity and insufficient structural stability of the polymer sulfur chains.

[0005] Therefore, it is necessary to provide a new composite material to improve the deficiencies of the prior art. Summary of the invention

[0006] In order to solve the deficiencies in the prior art, the present invention provides a MOF-based sulfide polymer composite material and a preparation method and application thereof. The present invention first uses a solvothermal method to prepare a zirconium-based metal organic framework material MOF808@PAA, then introduces defects to obtain a defective MOFs material, and then introduces sulfide polymers into the defective MOFs material to obtain a MOF-based sulfide polymer composite material. By introducing defects, the present invention enables the MOF-based sulfide polymer composite material to improve the pore size distribution and porosity of its framework structure while forming abundant active sites, thereby promoting the catalytic conversion kinetics of LiPS.

[0007] In order to achieve the above object, the specific scheme adopted by the present invention is: A method for preparing a MOF-based sulfide polymer composite material mainly comprises the following steps: S1. Add polyacrylic acid (PAA) to a mixed solution of DMF and formic acid, stir evenly by ultrasonication to obtain solution A, then add zirconium oxychloride and BTC to solution A, stir evenly at room temperature, then add carboxylated carbon nanotubes, stir evenly to obtain solution B containing MOF808@PAA; S2. Add 5-aminoisophthalic acid to solution B, stir evenly, then transfer to a reactor, perform hydrothermal reaction at 120° C. for 32 h, cool to room temperature after the reaction is completed, obtain mixed solution C, centrifuge the mixed solution C, and obtain MOF808-D@PAA; S3, washing, drying and grinding MOF808-D@PAA to obtain a powdery product; S4. Mix the powdered product with sulfur powder and catalyst evenly, transfer the mixture to a tubular furnace, and heat the mixture to 260°C at a heating rate of 5°C / min with argon as protective gas and keep the temperature for 2 hours to ensure that the elemental sulfur in the molten state is fully grafted with the PAA after decarboxylation coupling. After the reaction is completed, cool the mixture to room temperature, grind the cooled substance, place it in a reactor and diffuse it at 160°C for 16 hours, then centrifuge and wash it, and dry the centrifuged product to obtain a MOF-based sulfur polymer composite material.

[0008] Furthermore, in step S1, the volume ratio of DMF and formic acid is 1:1.

[0009] Furthermore, in step S3, MOF808-D@PAA was washed with DMF and dried in vacuum at 150° C. for 12 h.

[0010] Furthermore, in step S4, the mass ratio of the powdered product to the sulfur powder is 3:7.

[0011] Furthermore, in step S4, the catalyst is a mixture of KI, I2 and iodophenyldiacetic acid in a molar ratio of 2:1:1.

[0012] Furthermore, in step S4, the diffused sample was washed by alternating centrifugation with deionized water and ethanol at 8000 rpm, and the centrifuged product was dried under vacuum at 70 °C for 12 h.

[0013] On the other hand, the present invention provides a MOF-based sulfide polymer composite material, which is prepared by the above method.

[0014] In another aspect, the present invention provides an application of a MOF-based sulfide polymer composite material in a lithium-sulfur battery.

[0015] Beneficial effects: The present invention first uses a solvent thermal method to prepare a zirconium-based metal organic framework material MOF808@PAA, then adds 5-aminoisophthalic acid, introduces defective -NH2 to prepare a defective MOF808-D@PAA material, and finally combines with S to form a MOF-based sulfur polymer composite material MOF808-D@PS. The present invention introduces defects into the MOF808@PAA organic framework structure, improves the porosity while ensuring the uniform distribution of sulfur, and the exposure of a large number of Zr metal nodes greatly enhances the adsorption and catalytic conversion kinetics of LiPS. In addition, the unique design based on the MOF808-D molecular framework and using the PAA carbon chain as the main chain can achieve efficient loading of active sulfur, accelerate electron / ion transmission, promote the penetration of the electrolyte, optimize the reaction kinetics in its actual application process, promote its catalytic conversion kinetics, and promote the catalytic conversion of LiPS, inhibiting the serious dissolution and shuttle effect of LiPS. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic diagram of the preparation of Example 1.

[0017] Figure 2 This is the TEM image of the material obtained in Comparative Example 1.

[0018] Figure 3 This is the TEM image of the material obtained in Comparative Example 2.

[0019] Figure 4 This is the TEM image of the material obtained in Example 1.

[0020] Figure 5 This is the HETEM image of the material obtained in Comparative Example 1.

[0021] Figure 6are XPS spectra, wherein (a) is the XPS spectrum of the material obtained in Example 1; (bd) are the S 2p spectrum, Zr 3d spectrum and C 1s spectrum of the materials obtained in Example 1 and Comparative Example 2.

[0022] Figure 7 It is the first cycle charge and discharge curve diagram of the materials obtained in Example 1 and Comparative Examples 1-2.

[0023] Figure 8 It is a short cycle diagram of the materials obtained in Example 1 and Comparative Examples 1-2.

[0024] Fig. 9 It is the long cycle diagram of the materials obtained in Example 1 and Comparative Examples 1-2.

[0025] Fig.10 The impedance diagrams of the materials obtained in Example 1 and Comparative Examples 1-2 are shown. DETAILED DESCRIPTION

[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the protection scope of the present invention.

[0027] The present invention discloses a MOF-based sulfide polymer composite material and a preparation method and application thereof. The preparation method thereof is described in detail below. The preparation method thereof mainly comprises the following steps: S1. Add polyacrylic acid (PAA) to a mixed solution of DMF and formic acid (DMF: formic acid = 1:1, volume ratio), stir evenly by ultrasonication to obtain solution A, then add zirconium oxychloride and BTC to solution A, stir evenly at room temperature, then add carboxylated carbon nanotubes, stir evenly to obtain solution B containing MOF808@PAA; wherein, DMF and formic acid are for better dissolving organic PAA, and carboxylated carbon nanotubes are for improving the conductivity of the material; the amount of PAA added is 2-5 mmol, the amount of zirconium oxychloride is 0.4-0.7 mmol, the amount of BTC is 0.2-0.5 mmol, and the amount of 5-aminoisophthalic acid is 0.1-0.4 mmol, preferably, 3 mmol of PAA, 0.5 mmol of zirconium oxychloride, 0.3 mmol of BTC, and 0.2 mmol of 5-aminoisophthalic acid are selected; PAA contains carboxyl groups and has good electrochemical redox activity in LSBs; S2. Add 5-aminoisophthalic acid to solution B, stir evenly, then transfer to a reactor, perform hydrothermal reaction at 120°C for 32 hours, cool to room temperature after the reaction is completed, obtain mixed solution C, centrifuge the mixed solution C, and obtain MOF808-D@PAA; wherein 5-aminoisophthalic acid has a similar structure to BTC, and can introduce defective amino groups while being able to decarboxylate; S3, washing, drying and grinding MOF808-D@PAA to obtain a powdery product; S4. Mix the powdered product with sulfur powder and catalyst evenly, transfer the mixture to a tubular furnace, and heat the mixture to 260°C at a heating rate of 5°C / min with argon as protective gas and keep the mixture warm for 2 hours. On the one hand, the reaction can cause the carboxyl groups in PAA to undergo decarboxylation coupling reaction with polysulfide radicals to form sulfide polymers, and on the other hand, it can ensure that the elemental sulfur in the molten state is fully grafted with the PAA after decarboxylation coupling. After the reaction is completed, cool the mixture to room temperature, grind the cooled substance, and diffuse it in a reactor at 160°C for 16 hours to allow the sulfur to be more evenly dispersed. Then, wash the mixture by centrifugation, and dry the centrifuged product to obtain a MOF-based sulfide polymer composite material.

[0028] It should be noted that in step S4, the catalyst is a mixture of KI, I2 and iodophenyl diacetic acid in a molar ratio of 2:1:1. The catalyst can catalyze the decarboxylation process of the MOF material and the bonding process of sulfur and MOF.

[0029] Example 1 A method for preparing a MOF-based sulfide polymer composite material mainly comprises the following steps: S1. Add 0.216 g of polyacrylic acid (PAA) to 75 mL of a mixed solution of DMF:formic acid in a volume ratio of 1:1, and dissolve it completely by ultrasonication and stirring to obtain solution A. Add 0.171 g of zirconium oxychloride (ZrOCl2•8H2O) and 0.0756 g of BTC (1,3,5-benzenetricarboxylic acid) to solution A in sequence, mix well, then add 0.1 g of multi-walled carbon nanotubes (MWCNTs), and stir at room temperature for 15-20 min to disperse it evenly to obtain solution B containing MOF808@PAA. S2. Add 0.0364 g of 5-aminoisophthalic acid to solution B, stir evenly, transfer to a reactor, and perform hydrothermal reaction at 120°C for 32 h to introduce defects into the MOF808@PAA structure. After the reaction is completed and fully cooled, a mixed solution C is obtained. The mixed solution C is centrifuged at 8000 rpm for 3 min to collect MOF808-D@PAA. S3, washing the obtained MOF808-D@PAA three times with DMF solvent, and vacuum drying it at 150°C for 12 hours, and then grinding it with a mortar to make it into powder, so as to obtain a powdery product; S4. The powdered product was mixed with elemental sulfur in a mass ratio of 3:7, and 0.166 g of iodophenyl diacetic acid, 0.127 g of KI and 0.161 g of I2 were added in sequence, and the mixture was placed in a planetary ball mill and ball-milled at a speed of 160 rpm / min for 3-6 hours to make it evenly mixed; it was then transferred to a tubular furnace, and under the condition of argon as the protective gas, the temperature was increased to 260°C at a heating rate of 5°C / min and kept warm for 2 hours to ensure that the elemental sulfur in the molten state was fully grafted with the PAA after decarboxylation coupling. After the reaction was completed, it was cooled to room temperature, the cooled material was ground, and then placed in a reactor and diffused at a temperature of 160°C for 16 hours; thereafter, the diffused sample was alternately centrifuged and washed with deionized water and ethanol at a speed of 8000 rpm, and the washed product was vacuum dried at 80°C for 12 hours to finally obtain a MOF-based sulfur polymer composite material with a carbon chain as the main chain, which was recorded as MOF808-D@PS.

[0030] Comparative Example 1 0.216 g of polyacrylic acid (PAA) was added to 75 mL of a mixed solution with a volume ratio of DMF:formic acid = 1:1. After mixing evenly, 0.1 g of carboxylated carbon nanotubes (MWCNTs) was added and ultrasonically stirred to make them evenly dispersed. The mixture was hydrothermally reacted at 120°C for 32 hours and then vacuum dried at 150°C for 12 hours. The obtained solid material was mixed with elemental sulfur in a mass ratio of 3:7, and 0.166 g of iodophenyldiacetic acid, 0.127 g of KI and 0.161 g of I2 were added in sequence. The mixture was kept at 260°C for 2 hours to obtain a sulfur polymer composite material PS (without MOF808).

[0031] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the steps S2 and S3 are not included. The obtained product is a MOF808@PS composite material (without defects).

[0032] The products obtained in Example 1 and Comparative Examples 1-2 are analyzed below.

[0033] (1) TEM image analysis Figure 2 This is the TEM image of the material obtained in Comparative Example 1. Figure 3 This is the TEM image of the material obtained in Comparative Example 2. Figure 4 This is a TEM image of the material obtained in Example 1. Please refer to Figures 2 to 4The morphology of the material obtained in Comparative Example 1 is similar to that of most reported sulfur-containing polymers, a typical amorphous state, with severe aggregation and voids in the HRTEM image ( Figure 5 ).and Figure 2 In comparison, the material obtained in Comparative Example 2 ( Figure 3 ) and the material obtained in Example 1 ( Figure 4 ) shows a relatively smooth structure with an amorphous morphology. This may be caused by the introduction of MOF, which significantly reduces the aggregation of sulfur aggregates and enables better dispersion of sulfur. Figure 3 Compared with the material obtained in Example 1 ( Figure 4 The CNTs and sulfur polymers are obviously evenly distributed and present an ultra-thin porous structure. The good dispersion and ultra-thin nanoporous structure not only provide sufficient transmission channels for the efficient transmission of electrons / ions, but also provide sufficient space for the transportation and anchoring of sulfur.

[0034] (2) XPS analysis In order to analyze the surface chemical state of the synthesized sulfur-containing polymer, the products obtained in Example 1 and Comparative Example 2 were subjected to XPS analysis ( Figure 6 a) The measured spectrum confirmed the presence of C, S and Zr in the product obtained in Comparative Example 2, while the product obtained in Example 1 also combined N in addition to these elements. Figure 6 In b, the S 2p3 / 2 and S 2p1 / 2 peaks at 163.7 eV and 164.9 eV indicate SS bonds, while the peaks near 162.3 eV and 163.5 eV correspond to CS bonds. An increase of 0.2 eV in the binding energy of SS bonds in MOF808-D@PS was observed compared to MOF808@PS, indicating the presence of more elemental sulfur in MOF808@PS. The characteristic Zr 3d peaks at 182.8 eV and 185.2 eV ( Figure 6 c) corresponds to Zr 3d3 / 2 and Zr3d 5 / 2, respectively. This reflects the successful introduction of the MOF structure. The slight 0.1 eV shift in the lower binding energy in the product obtained in Example 1 relative to the product obtained in Comparative Example 2 can be attributed to the structural defects within the MOF framework of the product. In addition, these findings further verify the successful preparation of defective MOF-bonded sulfur-containing polymers.

[0035] (3) Electrochemical cycle test First, the composite materials obtained in Example 1 and Comparative Examples 1-2 are made into positive electrode materials, wherein the preparation method of the positive electrode material is as follows: the positive electrode materials are mixed according to the mass ratio of composite material: Ketjen black: binder = 7:2:1. PVDF, PVDF-HFP, sieved Ketjen black and CNTs are vacuum dried at 80 ° C for 8-12 h. A certain amount of N-methylpyrrolidone (NMP) solvent is added to the uniformly mixed PVDF and PVDF-HFP powders, and ultrasonic and oscillation are alternately performed until the powder is completely dissolved. After dissolution, the dried Ketjen black and CNTs are added, and ultrasonic and oscillation are continued until the powder is dissolved to obtain the binder required for the preparation of the composite material. According to a specific mass ratio, appropriate amounts of composite materials and Ketjen black are weighed respectively, and the powders are ground in the same direction until the powders are evenly mixed. Subsequently, a certain amount of binder is added to the evenly ground powder, and ultrasonic oscillation is performed for 5 min after stirring in a glass bottle for 20 min to make the slurry evenly mixed. Use a coater to evenly coat the obtained slurry on the current collector (carbon-coated aluminum foil), and place it in a vacuum drying oven at 60 °C for 12 h. Cut the dried electrode into small discs with a diameter of 12 mm and weigh them.

[0036] Battery assembly: CR2032 button cells are used and assembled in a super-purified glove box. Glove box parameters: The protective gas is high-purity argon (purity greater than 99.999%), the water content is less than 0.01 ppm, and the oxygen content is less than 0.01 ppm. First, the prepared cleaned and fully dried battery shell, shrapnel, gasket, 18 mm diameter diaphragm, and 12 mm positive electrode material are moved into the glove box. Subsequently, the battery is assembled, and finally the assembled battery is packaged with a button battery packaging machine, and the overflowed electrolyte is cleaned with non-woven fabric in time, and left for 12 hours at room temperature for testing.

[0037] Constant current charge and discharge test: The CT-4008T battery testing system produced by Shenzhen Xinwei Electronics Co., Ltd. was used to test the battery's cycle performance and rate performance. The test was maintained at room temperature, and the composite material was tested in a voltage range of 1.7-2.8 V to obtain the required cycle performance, rate performance and charge and discharge curve. The short cycle was 100 cycles and the long cycle was 500 cycles. Cyclic voltammetry test: The CHI660E electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd. was used to perform CV tests on the prepared samples. The parameter settings are as follows: the voltage range is 1.7-2.8 V, and the scan rate is 0.1 mV s -1 , 0.2 mV s -1 , 0.3 mV s -1 , 0.4 mV s -1 The test results are as follows: Figure 7-10 shown.

[0038] Depend on Figure 7 It can be seen that the composite material obtained in Example 1 has a -1 The first discharge capacity under the current density condition is 1272.4 mAh g -1 , while the composite material obtained in Comparative Example 1 only had a capacity of 774.2 mAh g -1 . Figure 8 The capacity retention rate of the composite material obtained in Example 1 after 100 cycles was 99.2%, and the capacity decay per cycle was only 0.008%, while the capacity retention rate of the composite material obtained in Comparative Example 2 was only 557.7 mAh g -1 .exist Fig. 9 In the long cycle diagram, it is obvious that at 0.3 A g -1 After 500 cycles at a current density of 1.34 Å, the composite material obtained in Example 1 still has a capacity of 692.5 mAh g -1 The specific capacity of Fig.10 Comparative analysis shows that the charge transfer impedance (Rct) of the composite material obtained in Example 1 is 30.72 Ω, which is much smaller than the charge transfer impedance of the material obtained in Comparative Example 2 (81.66 Ω) and the material obtained in Comparative Example 1 (149.87 Ω). In addition, the composite material obtained in Example 1 shows the steepest high-frequency straight line, indicating that it has the highest Li + Diffusion rate. This is because the MOF808-D@PS molecular framework material prepared in Example 1 not only retains the porous nanostructure of MOF808@PAA to a certain extent, but also exposes more metal active sites, promoting the catalytic conversion kinetics of LiPS.

[0039] It can be seen that the present invention, by introducing the MOF molecular framework into the composite material, improves the porosity of the sulfur polymer on the one hand, and on the other hand, can expose more metal sites with catalytic activity on the surface of the material to promote the transfer of electrons, thereby effectively improving the electrochemical performance of the battery. Compared with MOF808@PS and PS composite materials, MOF808-D@PS composite materials have a larger specific surface area and better pore size distribution. These characteristics not only help to load active sulfur, but also greatly alleviate the volume expansion generated during the cycle process.

[0040] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a MOF-based sulfide polymer composite material, characterized in that: The main steps are as follows: S1. Add polyacrylic acid to a mixed solution of DMF and formic acid, stir evenly by ultrasonication to obtain solution A, then add zirconium oxychloride and BTC to solution A, stir evenly at room temperature, then add carboxylated carbon nanotubes, stir evenly to obtain solution B containing MOF808@PAA; S2. Add 5-aminoisophthalic acid to solution B, stir evenly, then transfer to a reactor, perform hydrothermal reaction at 120° C. for 32 h, cool to room temperature after the reaction is completed, obtain mixed solution C, centrifuge the mixed solution C, and obtain MOF808-D@PAA; S3, washing, drying and grinding MOF808-D@PAA to obtain a powdery product; S4. Mix the powdered product with sulfur powder and catalyst evenly, transfer the mixture to a tubular furnace, and heat the mixture to 260°C at a heating rate of 5°C / min with argon as protective gas, and keep the temperature for 2 hours to ensure that the elemental sulfur in the molten state is fully grafted with the PAA after decarboxylation coupling. After the reaction is completed, cool the mixture to room temperature, grind the cooled substance, and then place it in a reactor to diffuse at 160°C for 16 hours, then centrifuge and wash it, and dry the centrifuged product to obtain a MOF-based sulfur polymer composite material.

2. The method for preparing a MOF-based sulfide polymer composite material according to claim 1, characterized in that: In step S1, the volume ratio of DMF and formic acid is 1:

1.

3. The method for preparing a MOF-based sulfide polymer composite material according to claim 1, characterized in that: In step S3, MOF808-D@PAA was washed with DMF and dried in vacuum at 150°C for 12 h.

4. The method for preparing a MOF-based sulfide polymer composite material according to claim 1, characterized in that: In step S4, the mass ratio of the powdered product to sulfur powder is 3:

7.

5. The method for preparing a MOF-based sulfide polymer composite material according to claim 1, characterized in that: In step S4, the catalyst is a mixture of KI, I2 and iodophenyldiacetic acid in a molar ratio of 2:1:

1.

6. The method for preparing a MOF-based sulfide polymer composite material according to claim 1, characterized in that: In step S4, the diffused sample was washed by alternating centrifugation with deionized water and ethanol at 8000 rpm, and the centrifuged product was vacuum dried at 70-80 °C for 12 h.

7. A MOF-based sulfide polymer composite material, characterized in that: The invention is prepared by the method described in any one of claims 1 to 6.

8. Use of the MOF-based sulfide polymer composite material according to claim 7 or the MOF-based sulfide polymer composite material prepared by the method according to any one of claims 1 to 6 in a lithium-sulfur battery.